Everyday disease diplomacy: an ethnographic study of diabetes self-care in Vietnam - Tine M. Gammeltoft; Thị Huyền Diệu Bùi; Thị Kim Dung Vũ; Đức Anh Vũ; Thị Ái Nguyễn; Minh Hiếu Lê (BMC Public Health, 2022)
Abstract Background Understanding people’s subjective experiences of everyday lives with chronic health conditions such as diabetes is important for appropriate healthcare provisioning and successful self-care. This study explored how individuals with type 2 diabetes in northern Vietnam handle the everyday life work that their disease entails. Methods Detailed ethnographic data from 27 extended case studies conducted in northern Vietnam’s Thái Bình province in 2018–2020 were analyzed. Results The research showed that living with type 2 diabetes in this rural area of Vietnam involves comprehensive everyday life work. This work often includes efforts to downplay the significance of the disease in the attempt to stay mentally balanced and ensure social integration in family and community. Individuals with diabetes balance between disease attentiveness, keeping the disease in focus, and disease discretion, keeping the disease out of focus, mentally and socially. To capture this socio-emotional balancing act, we propose the term “everyday disease diplomacy.” We show how people’s efforts to exercise careful everyday disease diplomacy poses challenges to disease management. Conclusions In northern Vietnam, type 2 diabetes demands daily labour, as people strive to enact appropriate self-care while also seeking to maintain stable social connections to family and community. Health care interventions aiming to enhance diabetes care should therefore combine efforts to improve people’s technical diabetes self-care skills with attention to the lived significance of stable family and community belonging.